ВОЛФРАМ ВА МОЛИБДЕН ГЕТЕРОПОЛИКИСЛОТАЛАРИ АСОСИДА ПЛАСТИКЛАШТИРИЛГАН МЕМБРАНАЛИ ИОН-СЕЛЕКТИВ МАТЕРИАЛЛАРНИ ИШЛАБ ЧИҚИШ ТЕХНОЛОГИЯСИ. - Абдурахмонова, Замира; Салимова, Шоҳиста; Суванқулов, Суванқулов Шохжахон Баҳодир ўғли; Абдурахманов, Эргашбой (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The composition of the electrodfaolic compound is recommended, and on its basis a highly sensitive ISE technology has been developed, which provides for the identification of various drugs. Developed selective ises are proposed for use as part of an ionomer device for monitoring medicinal substances.